Pengaruh Reading Habits terhadap Motivasi Belajar Mahasiswa di Fakultas Bahasa dan Seni Universitas Negeri Padang - Ayuningtiyas, Siti Azahra; Nabila, Jeihan (ARZUSIN, 2024)
This research aims to determine the influence of reading habits on student learning motivation at the Faculty of Languages and Arts, Padang State University. This research was carried out using a survey method with a quantitative type of research. The variables in this research are reading habits (X) and learning motivation (Y). The population of this study was 1326 people. The sample was taken from 100 respondents, namely students from the Faculty of Languages and Arts, Padang State University, class of 2022. The sampling technique used was simple random sampling. Data was collected using a questionnaire via Google Form with a Likert scale.Based on the research results, it is known that the average score for reading habits of students at the Faculty of Languages and Arts, Padang State University is 3.05 in the good category and the average score for learning motivation is 3.42 in the very good category. The influence of reading habits on student learning motivation at the Faculty of Languages and Arts, Padang State University with a significance of 0.00 < 0.05 with Fcount 169.331, then Ha is accepted and H0 is rejected. Therefore, reading habits have an influence on student learning motivation at the Faculty of Language Arts, Padang State University with a coefficient of determination of 0.633 or 63.3%. Thus, the influence of reading habits on student learning motivation at the Faculty of Languages and Arts, Padang State University is 63.3% and the rest is influenced by other factors not discussed in this research.